Kapabilitas Anak Sebagai Saksi Dalam Persidangan - Ksatria Anantiar Putra; Bima Aditya Ramadhan; Anak Agung Ngurah Bayu Adhi Perdana; Fadlan Razak; Abid Triasa; Novri Hardiansyah (Lembaga Pengembangan Kinerja Dosen, 2024)
A witness is a person who can provide information for the purposes of investigation, prosecution and justice regarding a criminal case that he himself heard, saw for himself and experienced for himself. The rules regarding the procedures for how a person can be presented as a defendant and then whether he will then be sentenced or not are regulated in a series of writings called the Criminal Procedure Law. In handing down a criminal decision, according to article 183 of the Criminal Procedure Code, a judge may not impose a crime on someone unless there are at least two pieces of evidence. One of the pieces of evidence that can be used by a judge is witness testimony. Children can be witnesses in a criminal trial. However, the validity of children's testimony is often still in doubt and further investigation is needed regarding the validity of children as witnesses in court. In Indonesia itself, the definition of child is regulated in various statutory regulations, including Law Number 23 of 2002 concerning Child Protection. A child is defined as someone who is not yet 18 (eighteen) years old, including children who are still in the womb. This article will explain more specifically the involvement of children as children in conflict with the law in the case of children who are witnesses to criminal acts, the position of children as witnesses in criminal trials, and the strength of the evidence of child witnesses' statements in criminal trials.